Acute orofacial pain leads to prolonged changes in behavioral and affective pain components. Issue 12 (December 2020) - Araya, Erika Ivanna; Baggio, Darciane Favero; Koren, Laura de Oliveira; Andreatini, Roberto; Schwarting, Rainer K. W.; Zamponi, Gerald W.; Chichorro, Juliana Geremias
Abstract : Abstract: Acute pain that persists for a few days is associated with a reduction in patients' quality of life. Orofacial persistent pain promotes psychological disorders such as anxiety, impairs daily essential activities such as eating, and results in decreased social interaction. Here, we investigated whether rats subjected to orofacial formalin injection or intraoral incision surgery display persistent facial heat hyperalgesia, ongoing pain, anxiety-like behavior, and changes in ultrasonic vocalization. Orofacial formalin injection or intraoral incision caused facial heat hyperalgesia for 3 days compared with saline-injected and sham animals. In addition, both experimental groups showed a reduction in the number of entries and in the time spent in the open arms in the elevated plus maze test on day 3, suggesting that anxiety-like behavior developed as a consequence of persistent pain. At this time point, both groups also displayed a reduction in the number of 50-kHz calls, specifically in the flat subtype, which suggests a decrease in social communication. Moreover, on day 3 after surgery, systemic morphine produced robust conditioned place preference in rats subjected to intraoral incision compared with sham, and the former group also presented increased spontaneous facial grooming, revealing the presence of ongoing pain. Finally, Western blot and immunohistochemistry analysis showed a reduction in tyrosine hydroxylase expression in the nucleus accumbens, which may reflect a decrease in mesolimbic dopaminergic activity. Altogether, the results demonstrate that acute orofacial pain causes prolonged changes in behavioral and affective pain components, which may be related to dopaminergic changes in the nucleus accumbens. Abstract : Acute orofacial pain causes prolonged changes in behavioral and affective pain components, which may be related to dopaminergic changes in the nucleus accumbens.